2007
DOI: 10.1158/0008-5472.can-07-0064
|View full text |Cite
|
Sign up to set email alerts
|

The SIL Gene Is Essential for Mitotic Entry and Survival of Cancer Cells

Abstract: Although mitosis is a general physiologic process, cancer cells are unusually sensitive to mitotic inhibitors. Therefore, there is an interest in the identification of novel mitotic inhibitors. Here, we report the novel discovery of the SIL gene as a regulator of mitotic entry and cell survival. The SIL gene was cloned from leukemia-associated chromosomal translocation. It encodes a cytosolic protein with an unknown function and no homology to known proteins. Previously, we observed an increased expression of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 16 publications
(20 reference statements)
3
48
0
Order By: Relevance
“…STIL is overexpressed in multiple cancers and its overexpression is associated with a metastatic phenotype and poor prognosis (Erez et al, 2004;Ramaswamy et al, 2003). In addition, knockdown of STIL in cancer cells delays entry into mitosis and induced apoptosis in several cancer cell lines (Erez et al, 2007). From these data, it might be speculated that overexpression of STIL in mammalian cells contributes to malignant transformation through the formation of supernumerary centrosomes, as observed for SAK in flies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…STIL is overexpressed in multiple cancers and its overexpression is associated with a metastatic phenotype and poor prognosis (Erez et al, 2004;Ramaswamy et al, 2003). In addition, knockdown of STIL in cancer cells delays entry into mitosis and induced apoptosis in several cancer cell lines (Erez et al, 2007). From these data, it might be speculated that overexpression of STIL in mammalian cells contributes to malignant transformation through the formation of supernumerary centrosomes, as observed for SAK in flies.…”
Section: Discussionmentioning
confidence: 90%
“…Alternatively, HeLa cells were transiently transfected with a vector encoding shRNA targeting STIL (pLKO.1, target sequence: 59-AAGACAACTGCTGTTGAAGAC-39) or control sequence (59-CAACAAGATGAAGAGCACCAA-39) (Erez et al, 2007).…”
Section: Rna Interferencementioning
confidence: 99%
“…Moreover, STIL expression was reported to be high in lung cancer (Erez et al, 2004) and most interestingly, mutations in STIL were recently shown to cause primary microcephaly (Kumar et al, 2009). Additional studies point to a possible role for STIL in cell proliferation, mitotic regulation and centrosome integrity (Izraeli et al, 1997;Campaner et al, 2005;Erez et al, 2007;Castiel et al, 2011), but the precise function of this protein remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Cytoplasmic protein SCL/TAL1 interrupting locus (SIL) is implicated in the mitotic activity and cellular proliferation of cancer cells (11)(12)(13). Sil null mouse embryos are lethal in the early stage of development with abnormal left-right specification (14), which are also found in sonic hedgehog (shh) null embryos (14)(15)(16), and double null embryos of sil and patched1, in which the intracellular Hedgehog (Hh) signaling should be constitutively activated, were phenotypically identical with sil null embryos (17).…”
Section: Introductionmentioning
confidence: 99%